Controlling Composite TiO2 Powder Characteristics in the Solid-State Synthesis of BaTiO3 Powders for Improved Sintering and Permittivity: A Comparative Study - Sang-Heun Lee; Yoon-Seok Lee; Jandi Kim; Ji-Hye Seo; Myunghee Cho; Hun Kwak; Ran-Sae Cheon; Seungchan Cho; Yangdo Kim; Kyoung-Seok Moon; Moonhee Choi (Applied Sciences, 2023)
In this study, the anatase–rutile phase fraction of TiO2, which would play a vital role in the solid-state synthesis of BaTiO3, was controlled to form a composite phase. The composite TiO2 was applied to a solid-state synthesis reaction, and the tetragonality, dielectric properties, and microstructure of the resulting BaTiO3 powders were analyzed under different synthesis conditions of TiO2. Furthermore, a comparative analysis of solid-state-synthesized BaTiO3 powders prepared using anatase, rutile, and mixed (anatase + rutile) TiO2 was performed to elucidate the mechanism of improvement in the sintering behavior and dielectric properties of the BaTiO3 powder synthesized using the composite TiO2. As a result of applying composite TiO2, BaTiO3 powder with excellent tetragonality was synthesized. In addition, it is effective in powder growth and the control of powder morphology, so sintering and dielectric properties can be improved at relatively low temperatures.